Rapid detection of Enterocytospora artemiae in Chinese grass shrimp (Palaemonetes sinensis) through isothermal recombinase polymerase amplification - Jiang, Hongbo; Liu, Jinghui; Bao, Jie; Xing, Yuenan; Feng, Chengcheng; Hu, Qingbiao; Li, Xiaodong; Chen, Qijun (Frontiers in Marine Science, 2022)
Enterospora artemiae, an obligate intracellular parasitic microsporidium, severely affects the development of Chinese grass shrimp (Palaemonetes sinensis) aquaculture. Currently, no effective drugs or vaccines are available for treatment. To improve diagnosis and prevention of microsporidia infection in P. sinensis, two recombinase polymerase amplification (RPA) detection methods (visualized by electrophoresis [RPA-AGE] and colloidal gold lateral flow dipstrip [RPA-LFD]) were established based on the E. artemiae S8 serine protease gene. RPA-AGE showed optimal amplification at 37 °C for 30 min, and RPA-LFD completed amplification in 10 min at 37 °C and produced detection results within 5 min. Regarding specificity, both methods showed specific amplification of E. artemiae but not of other pathogens. Regarding sensitivity, the minimum detection limit for RPA-AGE and RPA-LFD was 4.7 copies/μL. Using 30 clinical samples, the 70%-positive rate was lower than that of fluorescence quantitation, but accuracy was improved compared with conventional PCR (56.7%). Our RPA-AGE and RPA-LFD methods showed high specificity and sensitivity, with short detection time. In particular, the RPA-LFD method can be used for simple on-site detection of E. artemiae in P. sinensis farms without experimental equipment, which is important for prevention and control of this microsporidial disease.